Implementation Siri '- Na Pacce Through Learning Media In The Counseling Course Multicultural Through The LMS Application for Guidance and Counseling Students a Tadulako University - ., Nurwahyuni; Hanurawan, Fattah; ., Triyono; Rahmawati, Hetti; Ratu, Bau; ., Misnah (KnE Social Sciences, 2023)
This research was motivated by the lack of knowledge and understanding of students about regional culture related to SiricultureNapace in Guidance and Counseling (BK) students at Tadulako University. Thus it is necessary to trace these cultural values which will be developed into learning media in cross-cultural courses and will be implemented in online application learning using LMS. The application of learning in this multicultural cross-cultural course is to improve and develop the potential of Counseling Guidance Teachers for guidance and counseling students as graduates who have competencies that are able to compete in the era of globalization. The purpose of this research is to produce a description of the cultural values of Sirinapacce as cultural values in the Bugis Makassar community, which will be integrated into the learning process through online media design through the LMS application to improve the competence of BK students at Tadulako University. This study uses a qualitative descriptive research design by collecting and analyzing quantitative data which is then implemented in the learning process. The descriptive qualitative data search on the Na Paccesiri culture of the Makassar Bugis ethnic group was obtained from interviews, documentation, literature review. The findings of this study (1) the cultural values of Siri Na Pacce, namely SipakaingaSipaka tau, Sirimasiri, Toddopuli and Lambusu (2). Implement Na Paccesiri cultural values through online-based learning media. Keywords: Learning Media; LMS application; counseling guidance; online-based